Synthesize And Characterization Of Al2o3–, Batio3–, Tio2–, Cuo–Ccto Composites For Wideband Dielectric Resonator Application - Zaman, Rosyaini Afindi (2018)
Metallic antennas have been widely used in wireless communication system. In general this antenna is big in size with high tangent loss (tan δ) and the bandwidth is narrow with low efficiency. These shortcomings can be solved by using ceramic materials with high dielectric constant (εr) and low tan δ such as CaCu3Ti4O12 (CCTO), known as dielectric resonator antenna (DRA). At 8 GHz, εr is 62.76 and tan δ is 0.1458 and resonated between 8.56 to 9.12 GHz with 6.6% bandwidth. However, its tan δ is still considered as on the higher side (>0.1) and bandwidth coverage is less than 10% which is not able to cover a wider portion of the X band (8 GHz to 12 GHz) communication system. Therefore, to enhance the properties of DRA, CCTO properties can be modified through the addition with other oxides. In this research, Al2O3, BaTiO3, TiO2 and CuO, respectively, was added from 20, 40, 50, 60, and 80 wt% into CCTO. It was found that addition of Al2O3 has reduced εr to 37.33 but has improved tan δ value to the lowest value of 0.0520. This antenna resonated between 8.67 to 9.26 GHz with 5.61% bandwidth (addition 20 wt% Al2O3). The addition of BaTiO3 has increased εr to 85.23 with addition 80 wt% and tan δ in these series between 0.0627 – 0.0258. The result shows these composites resonated between 9.33 to 10.21 GHz with 8.91% bandwidth. The addition of 50 wt% of TiO2 shows εr of 56.47 and tan δ of these composites between 0.0165-0.1108, resonated from 10.03 to 11.36 GHz with 12.48% bandwidth. The highest εr (67.52) was obtained from 50 wt% CuO added to CCTO, improved tan δ (0.0203-0.0878) and resonated from 9.12 – 11.29 GHz with 21.26% bandwidth. These results show that all samples (mixtures) can be applied as DRA but mixture of 50CCTO/50CuO shows the best performance compare to others. For that reason, this mixture was further optimized and finally produced high εr (67.52), low tan δ (0.0141) and can also covered broader frequency range in X band which is suitable for the fabrication of a smaller DRA with better performance.